182k views
21 votes
6a - 8 = 4a + 6 i nee help

2 Answers

2 votes
Simplifying
6a + -8 = 4a + 6

Reorder the terms:
-8 + 6a = 4a + 6

Reorder the terms:
-8 + 6a = 6 + 4a

Solving
-8 + 6a = 6 + 4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4a' to each side of the equation.
-8 + 6a + -4a = 6 + 4a + -4a

Combine like terms: 6a + -4a = 2a
-8 + 2a = 6 + 4a + -4a

Combine like terms: 4a + -4a = 0
-8 + 2a = 6 + 0
-8 + 2a = 6

Add '8' to each side of the equation.
-8 + 8 + 2a = 6 + 8

Combine like terms: -8 + 8 = 0
0 + 2a = 6 + 8
2a = 6 + 8

Combine like terms: 6 + 8 = 14
2a = 14

Divide each side by '2'.
a = 7

Simplifying
a = 7
User Crlanglois
by
4.6k points
2 votes

Answer:

a=7

Explanation:

first subtract 4a from each side

6a-4a-8=6

than add 8 to each side

6a-4a=6+8

combine like terms

2a=14

divide both sides by 2

a=7

User Mohamed Adel
by
5.2k points